Phytochemical Composition, Anti-nutrient Properties and Antioxidant Potentials of Raw Hibiscus sabdariffa Seeds - Charles Nnanna Chukwu; Charity Uchechi Ogunka-Nnoka; Joyce Oronne Akaninwor (Archives of Current Research International, 2019)
Aims: This study was aimed at ascertaining the phytochemical, anti-nutrient and antioxidant potentials of raw seeds of Hibiscus sabdariffa (HS). Place and Duration of Study: Rivers and Anambra states, Nigeria, between January and April, 2017. Methodology: Dried seeds of Hibiscus sabdariffa were gotten from Mangu Local Government Area of Plateau state, Nigeria. They were properly cleaned, sorted and ground into powder for analyses. Phytochemical constituents and anti-nutrients were quantified using a BUCK M910 Gas chromatography equipped with an on-column automatic flame ionization detector (GC-FID) under standard chromatographic conditions. Antioxidant vitamins A, C and E were determined using standard spectrophotometric methods, while in vitro enzymatic antioxidants were determined using standard protocols. Results: The phytochemical screening revealed the presence of the following in their order of abundance: ribalidine>epicatechin>oxalate>catechin>saponin>sapogenin>kaempferol>tannin> lunamarine>rutin>anthocyanin>phytate>spartein. The anti-nutrient levels in the seeds of HS were: alkaloids (47.00 µg/ml; 39.20%), saponins (14.62 µg/ml; 12.19%), oxalates (14.06 µg/ml; 11.72%), tannin (4.79 µg/ml; 3.99%) and phytates (0.55 µg/ml; 0.46%). Antioxidant vitamins detected were vitamin A (2.76 ± 0.26 mg/kg), vitamin C (2.60 ± 0.07 mg/kg) and vitamin E (5.06 ± 0.30 mg/kg). Some in vitro enzymatic antioxidants were Catalase (26.71 ± 3.68 µmol/ml), Peroxidase (13.29 ± 1.72 µmol/ml), Glutathione reductase (24.43 ± 0.78 µmol/ml) and Superoxide Dismutase (0.88 ± 0.05 unit enzyme). Conclusion: Seeds of HS contain several phytochemicals which exist in great amounts, some of which may act as anti-nutrients that interfere with food absorption. Furthermore, HS seeds possess some antioxidant potentials which can be exploited for therapeutic purposes.